Гистологическое и гистохимическое исследование жирового тела мухи комнатной — Musca domestica L. (Diptera, Muscidae) на разных фазах созревания яичников - Карпенко, Л.В. (Вестник зоологии, 1973)
In Musca domestica L. females that have just flew out of puparia, the fatty body is presented,by two formations different in origin, microscopic structure, character of reserve accumulation: uni-nuclear cells of the larval fatty body and binuclear cells of the imaginal fatty body. The larval and imaginal fatty body takes an active part in ovary maturation. The ovarian follicles to phase Ha develop due to reserve substances of the larval fatty body which is completely utilized during the first days of the fly life. The further development of the ovaries is possible with valuable protein-carbohydrate nutrition of flies at the expense of protein substances contained in food and fats accumulating in cells of the imaginal fatty body and than entering the ovaries.